WOMEN'S EMPOWERMENT STRATEGY AS AN EFFORT INCREASING THE ROLE OF WOMEN IN NAGRAK VILLAGE SUKABUMI DISTRICT - Muhammad Adhitya Nugraha; Siti Nurbayani; Siti Komariah (Universitas Negeri Medan, 2024)
The lack of involvement of women in the development process has impacts especially on women themselves. There are aspirations that will be more effective if championed by women who specifically understand their needs. Women need to be empowered so they can function as subjects and objects in development. The aim of the research is to find out and analyze women's empowerment strategies as an effort to increase the role of women in Nagrak Village. This research uses a qualitative approach and descriptive methods. The results of the first research, the strategy for implementing women's empowerment programs as an effort to increase the role of women implemented by the Nagrak Village Government has 4 series of strategies, including; (1) field orientation, (2) inventory of problems and abilities, (3) personal approach, and (4) cooperation program. Second, the achievements of the women's empowerment program as an effort to increase the role of women by; (1) increasing involvement of women in various fields (2) increasing women's capacity by having understanding and skills. Third, there are 2 categories of obstacles faced by the Nagrak Village Government, namely; (1) internal barriers and (2) external barriers. Fourth, efforts that can be made to resolve existing problems include; (1) carry out consultations and coordination with the Sukabumi Regency Regional Government (through related agencies). (2) formulate and establish policies with a gender justice perspective. (3) building a partnership network with external parties.